'What Mrs Fisher knows about cooking' - on the titles of early American cookbooks - Magdalena Bator (Universitat Jaume I. Department of English Studies, 2023)
The proposed article aims to examine the strategies used by American women cookbook writers to attract the intended audience to their collections. The study is based on 19th-century cookbooks published in the United States; earlier collections, although available in the US were published in and brought from Britain. Written for and, in many cases, by housewives, the analysed cookbooks show, on the one hand, how the authors tried to convince the prospective reader of their expertise and knowledge. On the other hand, a certain degree of intimacy with the reader was to draw the reader's attention to the collection. The discussion will be based on (i) the cookbooks' titles, as they are "the first point of contact between the writer and the potential reader" (Haggan, 2004, p. 193) and an important determinant of a book's success; and (ii) the authors' signatures (as not all of the publications were signed with the author's name).